STRATEGI PEMERINTAH GAMPONG DALAM PEMBERANTASAN NARKOBA (Studi Gampong Matang Peupanji Kecamatan Lhoksukon Kabupaten Aceh Utara) - Ishak, Thanthawi; Miswar, Miswar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Drug trafficking is still rampant in the jurisdiction of the Lhoksukon Police. Several sub-districts in the city center are often used as places for transactions for these illicit goods. This is where the function and strategy of the Gampong Matang Peupanji Government as a representative of the North Aceh Regency government apparatus, especially regarding the implementation of the right strategy in the field is here. The purpose of the study was to determine the strategy of the gampong government in eradicating drugs in Gampong Matang Peupanji, Lhoksukon District and to find out the obstacles or obstacles faced by the gampong government in its efforts to eradicate drugs. The research methodology is to use qualitative research with a descriptive approach. The results of the study obtained data that the strategy of the Matang Peupanji Gampong Government in its efforts to eradicate drugs was first by compiling the Gampong Qanun or "Reusam Gampong" Matang Peupanji. Then the second, the Government of Gampong Matang Peupanji formed an anti-drug task force and volunteers in the village which was fully supported by the Muspika. Furthermore, the third, the Government of Gampong Matang Peupanji also strengthens the environmental security system in its area. The conclusion is that a strategy will be implemented effectively if the formulation, manufacture and implementation in the field are supported by actors, organizations, procedures and techniques with adequate facilities and infrastructure and carried out in a timely manner. The suggestion is that the Gampong Matang Peupanji Government is expected to have a high commitment in implementing its strategy for drug eradication.